Problematic use of online social networks: the case of Mexican students - Rubicelia Valencia-Ortiz; Urtza Garay-Ruiz; Julio Cabero-Almenara (Universidad Politécnica Salesiana, 2023)
Social networks are one of the most relevant means of communication and leisure among the youngest. But, despite an abundance of benefits, there are also risks that must be analyzed. In this research, the risk to be analyzed is the addiction to social media among young Mexican people. For the development of the analysis, 17,600 young people responded a questionnaire based on an adaptation of Sahin's Social Media Addiction Scale - Student Form (SMAS-SF). Among the results, it needs to be highlighted the little awareness that young people have of their addiction to social networks. Any reflection on this aspect needs to consider the limited perception presented by the sample and the fact that this study measured the self-perception of young students regarding OSM.